Initial Phase NT-proBNP, but Not Copeptin and High-Sensitivity Cardiac Troponin-T Yielded Diagnostic and Prognostic Information in Addition to Clinical Assessment of Out-of-Hospital Cardiac Arrest Patients With Documented Ventricular Fibrillation - Aarsetøy, Reidun; Aarsetøy, Hildegunn; Hagve, Tor-Arne; Strand, Heidi; Staines, Harry; Nilsen, Dennis W. T. (Frontiers in Cardiovascular Medicine, 2018)
Aim Sudden cardiac arrest (SCA) secondary to ventricular fibrillation (VF) may be due to different cardiac conditions. We investigated whether copeptin, hs-cTnT and NT-proBNP in addition to clinical assessment may help to identify the etiology of SCA and yield prognostic information. Methods and Results EDTA-blood was collected prior to or at hospital admission from patients with SCA of assumed cardiac origin. Clinical data were obtained from hospital records. VF was the primary heart rhythm in 77 patients who initially were divided into 2 groups based on whether they had an ischemic or non-ischemic mechanism as the most likely cause of SCA. They were further divided into 4 groups according to whether or not they had a history of previous heart disease. The patients were categorized by baseline clinical information, ECG, echocardiography and coronary angiography; Group 1 (n = 43): SCA with first AMI, Group 2 (n = 10): SCA with AMI and previous MI, Group 3 (n = 3): SCA without AMI and without former heart disease, Group 4 (n = 18): SCA without AMI and with known heart disease. Copeptin and hs-cTNT did not differ between patient groups, whereas NT-proBNP was significantly higher in patients with established heart disease without AMI and differed between non-AMI and AMI. Furthermore, NT-proBNP was significantly elevated in non-survivors as compared to survivors. Conclusion NT-proBNP provided both diagnostic and prognostic information in blood samples collected close to out-of-hospital resuscitation of VF patients, whereas copeptin and hs-cTnT failed to do so. Clinical Trial Registration ClinicalTrials.gov, NCT02886273.